Uma análise do modo argumentativo do discurso publicitário : uma temática de gênero social - Lima, Jane Kelly Silva de (2014)
Discourse analysis investigates the dimensions of the discursive event - text size, the dimension of discursive practice and the dimension of social practice - in order to understand how the discourse has results and effects on the relationships and social changes. In this sense, the discursive practice of Advertising manifests itself linguistically through multimodal texts that can be ideologically invested for the production, reproduction or transformation of relations of domination. Therefore, the objective of this research is to analyze advertising discourse in advertisements, aimed at the male and the female audience in mind the strategies of production, distribution and consumption, reflected the ideological issues of social gender. In pursuit of this purpose we adopt the theoretical perspective of Critical Discourse Analysis (FAIRCLOUCH, 2008), since it gives a social and linguistically oriented awareness of the effect of the speech in support or transformation of asymmetric power relations approach. In linguistics face dealing on the argumentative mode of discourse by proposing Charaudeau (2010) argumentative device also approach the linguistic brands present in the materials according to studies by Koch (2002) and Ducrot (1987), and also highlight the Interactive function postulated by Kress and Van Leeuwen (2006) according to the Grammar of Visual Design. Social orientation treat speech in relation to ideology and power, according to studies by Thompson (1995) and Fairclough (2008), and more precisely the focus of social gender relations defined by Scott (1989). The corpus of this study consists of 04 advertisements in the area of aesthetic drawn from print and electronic media, which were selected to present the same theme 'hair' for each target audience and chosen to represent different methods of hair removal in the market. The research is qualitative and analytical, and the methodological aspects we used visual and verbal resources of each piece for a description of the categories of analyzes based on the mentioned theoretical foundation. The investigation led us to conclude that the advertisements targeted at men and women perpetuate stereotypes of femininity and masculinity, ideologically helping to maintain asymmetrical power relations based on social gender. We believe that this research can bring contributions to the studies on the discursive constructions coated ideology which we enable and are also submitted. Thus, this work aims to reflect the social relations of gender, maintained and / or stated by advertising discourse by argument.